Madam President [large type] : a novel - Wallace, Nicolle (Thorndike Press, 2015)
President Charlotte Kramer is preparing for an in-depth day of interviews with CBS News -- a production that the White House refers to as a "Presidential Day in the Life." The purpose of the CBS filming is to pull back the curtain on President Kramer's second term White House, particularly now that she has all of the scandals of the first term behind her. Charlotte's new Press Secretary, Dale Smith, is charged with shepherding the two dozen news crews through the day. Dale and Charlotte have a complicated personal history, but they've been able to put the past behind them. Melanie Kramer, the country's secretary of defense, and one of President Kramer's closest advisors is also asked to participate. The perfectly scripted day is upended by a surprise critique from the President's own daughter. While the White House scrambles to prevent the family feud from overtaking the rest of the day's events, the White House staff hears news of an explosion in New York City. A few minutes later, they hear of more attacks. Soon it becomes clear that this is not typical day in the life of the White House. Rather, it's a day of terror and violence that the nation has not seen since September 11, 2001.